Open process frameworks patterns for the adaptive e-enterprise : with a case study in contract labor management - Marca, David A. (Emerging technologies, 2005)
Praise for Open Process Frameworks"From a customer experience standpoint, this conceptual approach to business design is a winner!" -Patricia Seybold, coauthor of Customers.com and The Customer Revolution "Marca illustrates . . . how the Internet can be used to create adaptive enterprises that dynamically change their processes, their rules, and their workers as their needs continually change. This book gives an enlightening glimpse of dramatic business opportunities now open to us." -Tom Malone, PhD, Patrick J. McGovern Professor of Management, MIT Sloan School of Management "Marca's Open Process Frameworks presents the essential business architecture to enable corporate adaptability in the twenty-first century . . .